Field evaluation of an electrostatic PM10 mass monitor used for continuous ambient particulate air pollution measurements - Artit Yawootti (2018)
© 2015 Elsevier B.V. The aim of this paper is to evaluate field values based on electrostatic charge technique of a PM10 mass monitor used for continuous measuring of ambient particulate air pollution. The PM10 mass monitor included electrostatic PM10 mass monitor (EPMM) and wireless monitor systems. In this study, the performance of the EPMM was simultaneously evaluated with a commercially available tapered element oscillating microbalance (TEOM) for measurements at ambient condition. The data of the sensor was connected to the internet through a GSM connection to a public cellular network. The monitoring data of ambient PM was collected and compared for both EPMM and TEOM by measuring at Chiang Mai City Hall during May 1st - 31st, 2015. The two different instruments showed good results that were highly correlated. The comparison between the EPMM and TEOM data values resulted in R2of 0.8352 and 0.9697, and a slope of 0.8401 and 0.9087 for 1-h and 24-h, respectively. In addition, it was found that the relative humidity played an important role in PM10 mass concentration and its electrical properties of the EPMM. Particularly the EPMM proved its advantages in measuring and detecting PM10 particulate air pollution for mass concentrations in the range from 0 to 500 μg/m3.